Biofilms formed within the acidic and the neutral biotrickling filters for treating H2S-containing waste gases. Issue 41 (12th May 2017) - Tu, Xiang; Guo, Jun; Yang, Yonggang; Feng, Rongfang; Sun, Guoping; Li, Jianjun
Abstract : Microbial cell in the innermost biofilm have higher viability, and produce polysaccharide as the main component of EPS in acidic environment. Abstract : Biofiltration of waste gases relies heavily on the biofilm on the surface of packing materials, whose formation has been believed to be associated with various environmental factors. In this study, we characterized two types of biofilms that are developed within an acidic and a neutral biotrickling filter (BTF), respectively. Both BTFs obtained near 100% removal efficiency when the H2 S inlet loading rate was lower than 12.5 g m −3 h −1 . As the rate was increased to 25 g m −3 h −1, however, the performance of the neutral BTF seemed to be compromised, with a decrease of 12.2% in removal efficiency, compared with a slight drop of 0.4% in the acidic one. The biomass in the neutral BTF ranged from 2.13 to 5.76 mgVSS gpacking −1, which was higher than that seen in the acidic BTF (from 1.22 to 4.64 mgVSS gpacking −1 ). Based on what was observed, we inferred that the stability of biofilms was influenced by the inlet loading rate and pH fluctuations. Besides, the ratio of planktonic cells : biofilm for the acidic BTF were higher than those of the neutral BTF, and polysaccharide was the dominant component of EPS. The maximum amounts of polysaccharide were 28.4 mg gVSS −1 for the neutral BTF and 156.2 mg gVSS −1 for the acidic one, while the corresponding protein amounts were only 11.2 and 5.4 mg gVSS −1, indicating that the polysaccharide in the EPS may play an important role in maintaining the mechanical stability of biofilm in extremely acidic conditions. Finally, we sampled some biofilms from the BTFs, whose three-dimensional structures were visualized by a confocal laser scanning microscopy (CLSM), and showed that the innermost layer of all biofilms exhibited the highest bacterial viabilities.